2007
DOI: 10.1007/s11010-007-9618-z
|View full text |Cite
|
Sign up to set email alerts
|

Modulations of rabbit erythrocyte ATPase activities induced by in vitro and in vivo exposure to ethanol

Abstract: Alcohol intake is associated with numerous degenerative disorders, and the detrimental effects of alcohol may be due to its influence on plasma membrane and cellular transport systems. The aim of the present study was to compare in vitro and in vivo effects of ethanol on rabbit erythrocyte ATPase activities and correlate them with ethanol-induced oxidative stress. Age-matched male rabbits were given 5% ethanol in 2% sucrose solution, for 6 weeks ad libitum; control animals were given tap water. Daily intake of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Ethanol is also capable to change the activities of the respiratory chain complexes, and the information on this is rather contradictory. For example, in the 1990s–2000s, studies appeared on the increase in the activity of ATPase under the action of ethanol [ 55 , 56 ]. At the same time, a decrease in the activity and expression of complexes in chronic alcoholism was also shown [ 39 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol is also capable to change the activities of the respiratory chain complexes, and the information on this is rather contradictory. For example, in the 1990s–2000s, studies appeared on the increase in the activity of ATPase under the action of ethanol [ 55 , 56 ]. At the same time, a decrease in the activity and expression of complexes in chronic alcoholism was also shown [ 39 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…By decreasing the activity of the Na-K-ATPase, moderate ethanol may decrease BBM glutamine co-transport by affecting the sodium gradient necessary for this co-transporter to properly function. Other studies have investigated the effect of ethanol on Na-K-ATPase activity and found that acute doses of ethanol decreased the activity of the Na-K-ATPase but chronic doses of ethanol increased its activity [33,34,35]. In all, while ethanol clearly has a wide range of effects on the Na-K-ATPase, the effect of moderate ethanol on the BLM Na-K-ATPase appears to have a role in regulating sodium-dependent nutrient assimilation by enterocytes ex vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, following treatment with ethanol, both cellular stress responses, such as the induction of heat shock protein 70, and immune responses, such as leukocyte infiltration and histamine release, were altered in the small intestine [ 1 , 41 , 59 ]. Increases in lipid peroxidation, reduction in antioxidants, and increases in oxidative stress have also been shown to occur in response to ethanol [ 61 , 62 , 63 ]. Overall, exposure to ethanol clearly alters intestinal homeostasis, including nutrient absorption [ 1 ].…”
Section: Alcohol Usementioning
confidence: 99%